Pengaruh Special Event “One Memorable Day With Oh Sehun” Terhadap Brand Image Skincare Whitelab (Survey Pada Pengunjung Special Event “One Memorable Day With Oh Sehun”) - Winda Krisnawati; Nani Nurani Muksin (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
One of the efforts made by the beauty company Whitelab to get consumers' attention is by attracting an actor from South Korea named Oh Sehun. The Whitelab company held a special event "One Memorable with Oh Sehun" as a way to improve its brand image and increase product sales. The aim of this research is to measure the influence of the special event "One Memorable Day with Oh Sehun" on the Whitelab skincare brand image. This research is quantitative research with a survey method and the data collection technique used is using a questionnaire. The sample data collection technique in this study used random sampling. The results of this research show that there is an influence between the special event "One memorable day with Oh Sehun" on the Whitelab skincare brand image on @Whitelab_id followers. This can be seen from the correlation coefficient value of 0.779 and the R Square value of 0.607 or 77.9%, this figure means that Whitelab's brand image was influenced by the special event "One Memorable Day with Oh Sehun", while the remaining 22.1% influenced by other variables not examined in this research.